Derivative development in the chiefly architecture of Línea Vieja: Two neighboring complexes of the Anita Grande archaeological site, Central Caribbean of Costa Rica - Vázquez Leiva, Ricardo (2022)
This article describes two neighboring architectural complexes that together form the monumental architecture of the Anita Grande site in the Línea Vieja region, Central Caribbean watershed of Costa Rica. We propose that these two complexes reflect the evolving chiefly status of the site’s residents. Ceramic analysis and radiometric data place the monumental construction to CE 950-1250, with evidence of occupations at the site in earlier periods. The information presented in this paper was collected from monitoring the site since 2004 and a field season of excavation in 2018. We conclude that the architectural construction at Anita Grande indicates chiefly authority, materialized through an initial design that was subsequently augmented, by a second complex 500 m away with aligned stone causeways.